The Effectiveness of Cognitive Strategies Towards Students’ Reading Comprehension at SMA Negeri 1 Sampaga - Annisa Kh, Nurun; Dollah, Syarifuddin; Munir, Munir (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The purposes of this study were; 1) to find out if the use of cognitive strategies is effective to improve students' reading comprehension at SMA Negeri 1 Sampaga or not, and 2) whether or not students are interested in utilizing cognitive strategies in their reading comprehension learning. This study employed a quantitative approach with a pre-experimental design. The population of this study was students in class X at SMA Negeri 1 Sampaga, and the sample was 16 students in class X at IPS 1. The research data were collected by providing a multiple-choice reading comprehension test on the subject of descriptive text, as well as a questionnaire on a Likert scale to measure students' interest. The t-test and descriptive statistics were used to analyze the data. According to the Paired Sample T-Test results, the probability value (sig. 2-tailed) = 0.000 which is lower than the significance level of 0.05. The researcher then concluded the use of the cognitive strategies is effective in improving students reading comprehension at SMA Negeri 1 Sampaga. Furthermore, the 'interested' response dominates the questionnaire score of the students’ interest. The findings indicated that students are interested in implementing cognitive strategies in their reading comprehension learning.Keywords— Cognitive Strategies, Reading Comprehension, Students’ Interest, Descriptive Text.